Internet GIS development for educational purposes. - Vassilopoulos, A.; Evelpidou, N. (Cartography, 2003)
Geographical Information Systems are important tools for various scientific aspects. Especially sciences related to cartography and geographical analysis should definitely employ GIS technology. In this study we present an Internet – based GIS that our team developed under MapXtreme platform. This application gives access to numerous web-users through a server that controls both analysis and data retrieval requests. It is a practical and economical method in order to introduce GIS to educational institutions. This Web GIS may operate through a local or wide area network and, apart from educational purposes, offers a low cost information exchange solution between vast numbers of users.